Continuous body impedance measurement to detect bladder volume changes during urodynamic study: A prospective study in pediatric patients. Issue 1 (16th November 2020) - Lee, Sangyeop; Moon, Junhyung; Shin, Seung‐chul; Hwang, Ji Hye; Lee, Kyoungwoo; Lee, Yong Seung
Abstract: Aims: To assess the possibility of the body impedance (BI) reflecting bladder volumes (BV) in pediatric patients, the BI signals are measured continuously with the equipment that we have developed and reported previously, during the filling phase of urodynamic study (UDS). Methods: A total of 30 children (5–12 years old) are included in this prospective study. The equipment uses two dry electrodes embedded inside a strap to collect impedance and electrocardiogram signals. The factors affecting baseline BI and its decreases during UDS have been investigated. Results: The median age is 6.1 years and BI is accurately measured in 27 out of 30 patients (90.0% accuracy). The median value of baseline BI is 1958 Ω. It is higher when they are older, equal to or taller than 125 cm, or non‐neurogenic bladder patients. BI decreases as the bladder is filled with saline in 21 patients (77.8%), and remains constant in 6 patients (22.2%). The median age of the Decreased Group is significantly higher than that of Nondecreased Group ( p = .036). Height of 125 cm or more is significant in the Decreased Group ( p = .020). Heart rates also have been simultaneously measured and revealed a mild decrease during the filling phase. Conclusions: The baseline BI is affected by the height and age of the children. BI is effectively measured and reflects a change in the BV in older children who are taller than 125 cm, with a small device using a smartphone and a strap.